The Influence of Organizational Culture, Leadership Style and Motivation on Employee Performance at the Bangil Religious Court - Valentine Mellityastiti; Hasan Ubaidillah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe and explain the influence of organizational culture, leadership style and motivation on employee performance at the Bangil Religious Court. This study uses a quantitative research type, which was conducted at the Bangil Religious Court using a Likert scale. The population and sample in this study were all employees at the Bangil Religious Court as many as 42 respondents and were taken using purposive sampling method. The source of data in this study is primary data obtained through observation and distributing questionnaires to all employees which is then processed using Statistical Product and Service Solution software version 22. Data analysis techniques use data quality tests, descriptive statistical analysis, classical assumption tests, regression analysis multiple linear and hypothesis testing. The results of this study indicate that simultaneously the variables of organizational culture, leadership style and motivation have a positive and significant effect on employee performance with a significance level of 0.000 <0.05 and a value of fcount > ftable which is 38,567.